Influência de parâmetros operacionais na microestrutura e propriedades mecânicas de ligas diluídas do sistema AL-ZN solidificadas através do processo squeeze casting - Silva, Diego Vilar da (2015)
The squeeze casting process is a casting process in which the cast metal in the liquid state is solidified under pressure in a metal mold closed off by a punch. In general components manufactured by squeeze casting have fine grained, high surface finish and almost free of porosity, may be the same of different sizes and shapes, the mechanical properties are enhanced significantly in comparison with the traditional method of casting and, in addition, parts manufactured by squeeze casting possess superior weldability and are able to heat treatment, and finally compared to the common casting parts manufactured by squeeze casting are formed in one operation with a lower energy consumption. The objective of this study is to analyze the influence of pressure as well as the zinc content of the alloys in the secondary dendrite spacing, the hardness and tensile strength limit, and correlate the microstructures with the mechanical properties and process parameters. For this purpose we used the mass compositions Al-Zn 1% Al-Zn 3% and Al-Zn 5% solidified with the squeeze casting process using the pressure 50 MPa, 100 MPa and 150 MPa, and the pressing time of 5 seconds. It is observed that the increase in pressure causes a reduction in dendrite spacing until 100 MPa, pressure variations from this point up to 150 MPa causes a increase in the secondary dendrite spacing, was also observed that the Vickers hardness and the tensile strength limit have a relationship with the secondary dendrite spacing.